Why is Nepal struggling to halt timber imports despite being rich in forest cover: A critical review from a theoretical lens? - Dangi, Resham Bahadur (Banko Janakari, 2025)
This paper unveils the historical background of timber production, trade, and revenue collection. It also delves into spatial dynamics and the countries’ competitiveness to evaluate the comparative advantage of timber industry. Furthermore, it analyzes the effects of tax, non-tax, and export duties on timber to explain- why timber import substitution became elusive. The paper concludes by suggesting market-driven royalty fees for NF/NIPF-produced softwood and transferring benefits of international best practices to make domestic timber competitive and substitute imports.